Counting Carbon: Calculative Activism and Slippery Infrastructure. Issue 5 (27th February 2017) - Beuret, Nicholas
Abstract : The environmental movement in the global North is in a state of impasse. It appears that despite the renewed international focus on climate change, and the actions of innumerable social movements, a "solution" to the problem appears as one, without a viable solution. It is the contention of this paper that climate change has no clearly viable solution as it is a seemingly impossible problem. This paper investigates how the problem of climate change is constructed as a global object of political action and how it functions to render politics into a matter of calculative action, one that seeks—but fails—to take hold of a slippery carbon infrastructure. It concludes by suggesting one possible solution to this dilemma is to turn away from the global scalar logic of climate change and towards a situated focus on questions of infrastructure, or what Dimitris Papadopoulos calls "thick justice".